Fluid and Thermodynamics Volume 1: Basic Fluid Mechanics - Hutter, Kolumban; Wang, Yongqi (Advances in Geophysical and Environmental Mechanics and Mathematics, 2016)
This first volume discusses fluid mechanical concepts and their applications to ideal and viscous processes. It describes the fundamental hydrostatics and hydrodynamics, and includes an almanac of flow problems for ideal fluids. The book presents numerous exact solutions of flows in simple configurations, each of which is constructed and graphically supported. It addresses ideal, potential, Newtonian and non-Newtonian fluids. Simple, yet precise solutions to special flows are also constructed, namely Blasius boundary layer flows, matched asymptotics of the Navier-Stokes equations, global laws of steady and unsteady boundary layer flows and laminar and turbulent pipe flows. Moreover, the well-established logarithmic velocity profile is criticised.